Ethnic networks and location choice of immigrants - Sholeh A. Maani (IZA World of Labor, 2016)
Immigrants can initially face significant difficulties integrating into the economy of the host country, due to information gaps about the local labor market, limited language proficiency, and unfamiliarity with the local culture. Settlement in a region where economic and social networks based on familiar cultural or language factors (“ethnic capital”) exist provides an effective strategy for economic integration. As international migration into culturally diverse countries increases, ethnic networks will be important considerations in managing immigration selection, language proficiency requirements, and regional economic policies.
Keywords: J23; J30; J31; J61; Z13; Z18; 330; migrants; ethnic capital; networks; economic resources; location choices